TINJAUAN HUKUM PENGUASAAN TANAH OLEH WARGA DI KECAMATAN TANJUNGSARI KABUPATEN SUMEDANG TERHADAP JALUR KERETA API NONAKTIF - Ulima Fhadiah Ermahri; Betty Rubiati; Mulyani Djakaria (Faculty of Law - Tarumanagara University, 2021)
Development in the transportation sector raises various land problems. One of them is the problem of land tenure without rights that occurs on the non active railroad. This problem arises because the residents live on the land of the former railroad track that has been inactive for a long time, such as what happened in Tanjungsari District, Sumedang Regency. The plan to reactivate the Rancaekek-Tanjungsari railway line is the beginning of problems related to land tenure. This study aims to determine how the legal status of the railroad tracks non active in Tanjungsari District, Sumedang Regency and how to solve the land problems. The research method used is juridical normative, the research specification is descriptive analysis. The method used is normative juridical analytical descriptive research. Based on secondary data and data collection using literature studies and interviews. The data analysis method used in this research is qualitative juridical. Based on the results of this study, it can be concluded that the legal status of land controlled by residents is assets belonging to PT KAI, which is state land controlled by PT KAI on the basis of mastery in the form of grondkaart. The residents occupied the land without rights. Therefore, in an effort to resolve the land issue, deliberation / mediation is necessary to find the best solution by taking into account the interests of the related parties, or it can be resolved by public consultation.